First Carpometacarpal Joint Anatomy and Osteoarthritis: MR Imaging Overview - Kamalasekar, Kanagasabai; Ravikanth, Reddy (Indian Journal of Radiology and Imaging, 2021)
The first carpometacarpal (CMC) joint consists of seven ligaments. The magnetic resonance imaging (MRI) examination of the first CMC joint should be performed in a high field 1.5/3 T MRI with a dedicated hand coil for high-resolution images. Degeneration of anterior oblique ligament (AOL) is the most important cause for the development of osteoarthritis of first CMC joint. Since the AOL undergoes a predictable pattern of alteration at its metacarpal attachment as degeneration proceeds, MRI imaging can provide an accurate assessment of this ligament.
Keywords: anterior oblique ligament; first carpometacarpal joint; osteoarthritis